Creating Culture through Health Leadership - Svedin, Lina M. (Book collections on Project MUSE., 2020)
"Disparities in health and wellness are intrinsically linked with local physical and socioeconomic disparities, but also to a sense of community. In the face of structural inequities and lack of access to needed health care, America needs leaders to guide communities toward a culture of health. This book represents a practitioner's view on community engagement and how we can build a culture of health through community grown solutions. The contributors discuss how each exercises community action, organizes and educates to reduce disparities in health, and works to increase access to community resources"--